Earnings and Stock Splits - Asquith, Paul; Healy, Paul; Palepu, Krishna (The Accounting Review, 1989)
[This paper examines whether stock splits convey information about earnings. The results indicate that firms split their shares after a significant increase in earnings. Before the stock split announcement, the market expects these earnings increases to be temporary. The split announcement leads investors to increase their expectations that the past earnings increases are permanent. The evidence also suggests that the market's reaction to split announcements cannot be attributed to expectations of either future earnings increases or near-term cash dividend increases.]